Laras and Surupan in the Song Panghudang Rasa by Eutik Muchtar: a Study of Sundanese Kepesindenan - Maulana, Marsel Ridky; Sutanto, Toni Setiawan (Universitas Negeri Medan, 2024)
The song “Panghudang Rasa” is one of the musical repertoires in the form of sekar-gending that is often presented in Kliningan and Wayang Golek performances. Eutik Muchtar's work is known to have a high level of musical difficulty, especially in the kepesindenan genre. This research aims to uncover the song's musical uniqueness, which includes the use of multi-laras, complex surupan variations, and deep poetic meanings. Using a descriptive qualitative method, this research analyzes audio and video recordings to identify its musical structure. The results show that this song uses Dwi-Laras, namely Degung and Madenda laras, with nine surupan: Madenda 4= Tugu, Madenda 4= Panelu, Madenda 5= Tugu, Madenda 2= Tugu, Madenda 5= Galimer, Madenda 2= Galimer, Degung 2= Tugu, Degung 3= Panelu, and Degung 5= Tugu. The song combines vocal and musical aspects, resulting in a complex and aesthetic structure. This finding confirms that “Panghudang Rasa” is a work that is not only beautiful in terms of musical aesthetics, but also rich in philosophical values.